Taxonomy of Late Jurassic diplodocid sauropods from Tendaguru (Tanzania) - K. Remes (Fossil Record, 2009)
The Late Jurassic (Tithonian) Tendaguru Beds of Tanzania yielded one of the richest sauropod faunas known, including the diplodocines Tornieria africana (Fraas, 1908) and Australodocus bohetii Remes, 2007, the only known representatives of their group on the southern continents. Historically, the holotypes and referred material of both taxa plus dozens of additional specimens had been subsumed under the term "Barosaurus africanus" (Fraas, 1908). Here, the taxonomic status of the referred elements is reviewed by evaluating the phylogenetic information content of their anatomical characters, in order to provide a firm footing for further studies (e.g. of morphometrics, histology, and phylogeny of the Tendaguru sauropods). Some of the material shows diplodocine synapomorphies and may belong to either Tornieria or Australodocus, while other specimens are diagnostic only on higher taxonomic levels (Diplodocidae, Flagellicaudata, or Diplodocoidea indet.). The isolated limb elements in most cases lack phylogenetically diagnostic characters. Generally, the "Barosaurus africanus" sample shows a substantial grade of morphological variation, and it cannot be ruled out that there are more flagellicaudatans represented in the Tendaguru material than the diplodocines and dicraeosaurids already known. doi:10.1002/mmng.200800008